Five Pneumonia Cases Associated with Visceral Leishmaniasis in Turkey - Totan M.; Hokelek M.; Cetinkaya M.C. (My University, 2003)
Visceral leishmaniasis (VL) is a parasitic infection that is endemic in the Mediterranean with a predilection to early childhood. This study included five children having pneumonia among 50 children diagnosed as VL between January 1980 and March 2002. The medical records of patients were evaluated retrospectively. Of these, three were male and two were female. The mean age was 4.2 ± 0.9 years. Fever, a nonproductive cough, and splenomegaly were found in all patients. Leishmania donovani was identified by microscopic examination of the bone marrow smears in our cases. Anemia, leukopenia, neutropenia, thrombocytopenia, and pancytopenia were found in 100%, 80%, 60%, 60%, and 60% of our cases, respectively. Formol-gel test were positive in all patients. The predominant pathogens isolated from blood specimens were Staphylococcus aureus and Streptococcus pneumoniae. In chest X-ray, there were bronchopneumonic infiltration in three patients and lober pneumonia in two patients. All patients were treated with meglumine antimonate for leishmaniasis and with antibiotic treatment for pneumonia. All the children were finally cured and no recurrence and death was observed. We consider that the children with VL should be carefully investigated for pneumonia.
Keywords: Pneumonia; Visceral Leishmaniasis (VL)